Kroppens mareridt og kroppens lyst: sanselige formidlinger i grønlandske kriminalromaner (Arctic Noir) - Rygaard, Jette (Grønlandsk Kultur- og Samfundsforskning, 2024)
The Body’s Nightmare: Sensuous Arctic Noir The works of Mads Peder Nordbo have attracted the attention of audiences from around the globe by incorporating elements of the Arctic Noir genre into a uniquely Greenlandic setting. Drawing on the framework established by French philosopher Michel Serres in his analyses of the phenomenology of sense perception as well as the work of feminist scholar bell hooks on ideas of healing love, this article explores Nordbo’s use of sensory experience in his novels. Focusing on Nordbo’s use of the vastness, desolation, and cold of the Arctic environment as an opponent as dangerous as any human killer with a revolver, this article examines how the full sensory experience of nature in conjunction with the human struggle create an almost unbearable tension which is faced simultaneously by the reader and the works’ protagonists.